Virtual resource provision with enhanced QoS in cloud platforms. (2015) - Liu, Dongbo; Yang, Gaobo
With the development of cloud computing, quality of service (QoS) becomes an important issue in many practical cloud platforms. Unfortunately, there is still no integrated framework or middleware that can provide desirable QoS in cloud environments. In this paper, we propose a QoS-aware virtual resource provision for cloud (QVRP-CLOUD) framework to achieve this goal. In the QVRP-CLOUD, a novel virtual machine (VM) reservation mechanism, namely relax reservation, is implemented for improving the adaptive of resource provision especially when the cloud system is in presence of intensive resource requirements. Extensive experiments are conducted to investigate the effectiveness and performance of the proposed framework. And the results shown that it can significantly improve many important QoS metrics, which in turn improves the cloud user's QoS satisfactory.